Kontekstualisasi Konsep Keluarga Sakinah: Pergulatan Pemikiran Hukum Keluarga dalam Tafsir Al Qur’an/The Contextualization of the Sakinah Family Concept: The struggle for family law ideas in the interpretation of the Qur'an - Sholehudin, Miftahus (Fakultas Syariah, 2020)
Abstract: The sakinah family is the ideal marriage destination according to the Koran. Various ways were taken to achieve this goal. However, people understand the concept of the Sakinah family differently. Differences in views on the concept of the sakinah family are also found in the thoughts of experts in the commentator of the Koran. This article is the result of doctrinal law research with historical approach and conceptual approach. The results of this study indicate that the meaning of the sakinah concept cannot be separated from the socio-cultural background of the interpreters. Imam Qurtuby and Ibn Kathir represent the context of fiqh in interpreting the sakinah family. The concept of the sakinah family tends to be interpreted as a process of realizing the biological function of the family. Imam Thabaryy became a specific commentator adding social functions in realizing the Sakinah family not only a biological function.Keywords: sakinah conception; exegesis; mufassirAbstrak: Keluarga sakinah merupakan tujuan perkawinan yang ideal menurut Al Quran. Berbagai cara ditempuh untuk mewujudkan tujuan tersebut. Namun, masyarakat memahami konsep keluarga sakinah secara berbeda-beda. Perbedaan pandangan terhadap konsep keluarga sakinah juga ditemukan dalam pemikiran para ahli tafsir Al Quran. Artikel ini merupakan hasil penelitian hukum doctrinal dengan pendekatan sejarah dan pendekatan konseptual. Hasil kajian ini menunjukkan bahwa pemaknaan konsep sakinah tidak terlepas dari latar sosio kultural dari para ahli tafsir. Imam Qurtuby dan Ibnu Kathir menjadi representasi konteks fikih dalam memaknai keluarga sakinah. Konsep keluarga sakinah cenderung dimaknai sebagai proses realisasi fungsi biologis keluarga.Â Imam Thabaryy menjadi mufasir yang spesifik menambahkan fungsi sosial dalam mewujudkan keluarga sakinah tidak hanya fungsi biologis.Kata Kunci: konsep keluarga sakinah; tafisr; ahli tafsir.